Metamodel-based Markov-Chain-Monte-Carlo parameter inversion applied in eddy current flaw characterization. (October 2018) - Cai, Caifang; Miorelli, Roberto; Lambert, Marc; Rodet, Thomas; Lesselier, Dominique; Lhuillier, Pierre-Emile
Abstract: Flaw characterization in eddy current testing usually requires to solve a non-linear inverse problem. Due to high computational cost, Markov Chain Monte Carlo (MCMC) methods are hardly employed since often needing many forward evaluations. However, they have good potential in dealing with complicated forward models and they do not reduce to only providing the parameters sought. Here, we introduce a computationally-cheap surrogate forward model into a MCMC algorithm for eddy current flaw characterization. Due to the use of a database trained off-line, we benefit from the MCMC algorithm for getting more information and we do not suffer from the computational burden. Numerous experiments are carried out to validate the approach. The results include not only the estimated parameters, but also standard deviations, marginal densities and correlation coefficients between two parameters of interest.